Contractile properties of isolated muscle spindles of the frog - Edman, K A P (Blackwell Science Inc, 2002)
Force and isotonic shortening velocities were studied (0.6-4.0 °C) in isolated single muscle spindles from the anterior tibialis muscle of Rana temporaria using techniques that enabled measurements both from the spindle as a whole and from marked segments of the preparation. The force-velocity relationship during tetanic stimulation exhibited the same biphasic shape as previously described for extrafusal muscle fibres. However, the maximum speed of shortening of the spindle fibres was merely 0.95 ± 0.006 lengths s(−1) (mean ± s.e.m., n = 11), which is approximately half the value recorded in extrafusal fibres of the same muscle. The maximum tetanic force, 91 ± 10 kN m(−2), n = 14, was likewise only approximately half that produced by extrafusal fibres. The force generated by the capsule segment was lower than that produced by the whole spindle resulting in elongation of the capsule region during a fixed-end tetanus. The intracellular calcium ion concentration reached during the plateau of the tetanus, 1.7 ± 0.1 μM (n = 8), was substantially lower than the value attained in extrafusal fibres under equivalent conditions. In accordance, the spindle fibres did not become fully activated during supramaximal electrical stimulation as indicated by the finding that the tetanic force could be further increased by 16.6 ± 0.04 % (n = 5) on addition of 0.5 mm caffeine. Inadequate activation may thus, to a certain extent, account for the relatively low force per cross-sectional area of the spindle fibres. The contractile properties of the intrafusal fibres should make the spindle organ suited to provide feedback control during eccentric (forced lengthening) and static (isometric) contractions and, with reduced effectiveness, during slow muscle shortening.